Du crépuscule à l’aube - Cathy Toupin (Temporalités, 2006)
Among the work characteristics that are likely to influence age and experience related adjustment processes, the issue of work schedules remains largely unexplored. We believe however that work schedules or shifts play an important part in building and mobilizing experience. This paper aims at characterizing the specific strategies implemented by night shift personnel based on a study conducted with nurses in a hospital department of pulmonary diseases. It also suggests a dynamic approach regarding the links between work shifts and the work activity, pointing out how such links evolve over the course of a career as a result of experience, and how such a process is “visible” in their activity at present. Nurses in the pulmonary disease department “assign” themselves goals; they devise a “night interpretation” of their task, taking into account the condition of their patients (goals aimed at protecting their sleep and calming their anxiety), the absence of health care staff resulting in a deserted environment (goals aimed at ensuring they are always well informed on the state of each patient), and their own psycho-physiological state (goal aimed at remaining alert). Their experience of night work allows them, on the one hand to recognize the aims of such actions, and identify the contradictions that may arise from them; and on the other hand to compensate for the difficulties and disturbances caused by such “tensions” by finding ways to compromise.